Dopamine D2 receptor agonist, bromocriptine, remodels adipose tissue dopaminergic signalling and upregulates catabolic pathways, improving metabolic profile in type 2 diabetes - G. Tavares; D. Marques; C. Barra; D. Rosendo-Silva; A. Costa; T. Rodrigues; P. Gasparini; B.F. Melo; J.F. Sacramento; R. Seiça; S.V. Conde; P. Matafome (Elsevier, 2021)
Background and objectives: The therapeutic effects of the dopamine D2 receptor (D2R) agonist, bromocriptine, in type 2 diabetes (T2D) have been attributed to central nervous system actions. However, peripheral dopamine directly modulates glucose uptake in insulin-sensitive tissues and lipid metabolism in adipose tissue (AT). We hypothesized that the dopaminergic system may be impaired in the adipose tissue of patients with T2D and that the therapeutic actions of bromocriptine could involve the modulation of metabolism in this tissue. Methods: The expression of dopamine receptors was evaluated in visceral AT samples from patients with obesity and stratified in several groups: insulin sensitive (IS); insulin resistance (IR) normoglycaemic; insulin resistant prediabetic; insulin resistant diabetic, according to Ox-HOMA2IR, fasting glycaemia and HbA1c levels. T2D Goto-Kakizaki rats (GK) were fed a high-caloric diet (HCD) for five months and treated with bromocriptine (10 mg/kg/day, i.p.) in the last month. The levels of dopaminergic system mediators and markers of insulin sensitivity and glucose and lipid metabolism were assessed in the peri-epididymal adipose tissue (pEWAT) and brown (BAT) adipose tissues, liver, and skeletal muscle. Results: Patients with IR presented a decreasing trend of DRD1 expression in the visceral adipose tissue, being correlated with the expression of UCP1, PPARA, and insulin receptor (INSR) independently of insulin resistance and body mass index. Although no differences were observed in DRD2, DRD4 expression was significantly decreased in patients with prediabetes and T2D. In HCD-fed diabetic rats, bromocriptine increased D1R and tyrosine hydroxylase (TH) levels in pEWAT and the liver. Besides reducing adiposity, bromocriptine restored GLUT4 and PPARγ levels in pEWAT, as well as postprandial InsR activation and postabsorptive activation of lipid oxidation pathways. A reduction of liver fat, GLUT2 levels and postprandial InsR and AMPK activation in the liver was observed. Increased insulin sensitivity and GLUT4 levels in BAT and an improvement of the overall metabolic status were observed. Conclusions: Bromocriptine treatment remodels adipose tissue and the liver dopaminergic system, with increased D1R and TH levels, resulting in higher insulin sensitivity and catabolic function. Such effects may be involved in bromocriptine therapeutic effects, given the impaired expression of dopamine receptors in the visceral adipose tissue of IR patients, as well as the correlation of D1R expression with InsR and metabolic mediators.